Physical and chemical analysis of different types of milk in relation to the presence of milk adulteration - Masarudin, Siti Nor Atiqah (2017)
The immense rely of Malaysia on imported products caused the tariff rates on dairy products to be much lower as compared to other foods and dairy imports licenses became more readily obtained. The general objective of this research is to determine the presence of milk adulteration of milk from different types while specific objectives include; determining the physical characteristics and chemical analysis of milk samples performed for detection of signs of adulteration. Samples were divided into three categories namely Fresh milk, UHT milk and Imported Fresh milk based on their packaging labels. The physical analysis includes the determination of pH using a pH meter and the measurement of specific gravity through the use of lactometer. Chemical analysis incorporates the detection of formalin with the addition of concentrated suphuric acid, detection of starch using iodine solution and the detection of skim milk powder by testing milk samples with nitric acid. Results showed that majority of milk samples acquired an alkaline pH and a low specific gravity related to the addition of water in milk as well as having a significant difference between milk samples with a value of (P<0.05). Detection of formalin showed a 100 % for both Fresh and Imported Fresh milk while 87 % for UHT milk. Starch and skim milk powder detection was 100 % negatively tested for samples of all three milk types.